Mechanochemistry of supramolecules - Bose, Anima; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2019)
The urge to use alternative energy sources has gained significant attention in the eye of chemists in recent years. Solution-based traditional syntheses are extremely useful, although they are often associated with certain disadvantages like generation of waste as by-products, use of large quantities of solvents which causes environmental hazard, etc. Contrastingly, achieving syntheses through mechanochemical methods are generally time-saving, environmentally friendly and more economical. This review is written to shed some light on supramolecular chemistry and the synthesis of various supramolecules through mechanochemistry.
Keywords: ball milling; mechanochemistry; self-assembly; solvent-free; supramolecular

(untitled) - Ruiz-Mirazo, K.; Briones, C.; de la Escosura, A. (Chem. Rev., 2014)

(untitled) - Peyralans, J. J.; Otto, S. (Curr. Opin. Chem. Biol., 2009)

(untitled) - Li, J.; Nowak, P.; Otto, S. (J. Am. Chem. Soc., 2013)

(untitled) - Zarra, S.; Wood, D. M.; Roberts, D. A.; Nitschke, J. R. (Chem. Soc. Rev., 2015)

(untitled) - Zhang, G.; Mastalerz, M. (Chem. Soc. Rev., 2014)

(untitled) - Wilson, A.; Gasparini, G.; Matile, S. (Chem. Soc. Rev., 2014)

(untitled) - Bowman-James, K. (Acc. Chem. Res., 2005)

Perspectives in Supramolecular Chemistry - Cramer, F. (Emil Fischer's Lock-and-Key Hypothesis after 100 years-Towards a Supracellular Chemistry, 2007)

(untitled) - Lehn, J.-M. (Angew. Chem., Int. Ed. Engl., 1988)

(untitled) - Mahadevi, A. S.; Sastry, G. N. (Chem. Rev., 2016)

(untitled) - Cougnon, F. B. L.; Sanders, J. K. M. (Acc. Chem. Res., 2012)

(untitled) - Zhang, D.; Ronson, T. K.; Nitschke, J. R. (Acc. Chem. Res., 2018)

(untitled) - Percástegui, E. G.; Mosquera, J.; Ronson, T. K.; Plajer, A. J.; Kieffer, M.; Nitschke, J. R. (Chem. Sci., 2019)

(untitled) - Haynes, C. J. E.; Zhu, J.; Chimerel, C.; Hernández-Ainsa, S.; Riddell, I. A.; Ronson, T. K.; Keyser, U. F.; Nitschke, J. R. (Angew. Chem., Int. Ed., 2017)

(untitled) - Miljanić, O. Š. (Chem, 2017)

(untitled) - Islam, S.; Powner, M. W. (Chem, 2017)

(untitled) - Ashkenasy, G.; Hermans, T. M.; Otto, S.; Taylor, A. F. (Chem. Soc. Rev., 2017)

(untitled) - Mattia, E.; Otto, S. (Nat. Nanotechnol., 2015)

(untitled) - Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - de la Hoz, A.; Díaz-Ortiz, Á.; Moreno, A. (Chem. Soc. Rev., 2005)

(untitled) - Toda, F. (Acc. Chem. Res., 1995)

(untitled) - Toda, F.; Tanaka, K.; Iwata, S. (J. Org. Chem., 1989)

Sonochemistry and the Acoustic Bubble - Kimura, T. (Application of Ultrasound to Organic Synthesis, 2015)

(untitled) - Baig, R. B. N.; Varma, R. S. (Chem. Soc. Rev., 2012)

(untitled) - Varma, R. S. (Green Chem., 2014)

(untitled) - Cravotto, G.; Gaudino, E. C.; Cintas, P. (Chem. Soc. Rev., 2013)

(untitled) - Braga, D.; Maini, L.; Grepioni, F. (Chem. Soc. Rev., 2013)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Ley, S.; O'Brien, M.; Denton, R. (Synthesis, 2011)

(untitled) - Achar, T. K.; Maiti, S.; Mal, P. (RSC Adv., 2014)

(untitled) - Bose, A.; Mal, P. (Tetrahedron Lett., 2014)

(untitled) - Walsh, P. J.; Li, H.; de Parrodi, C. A. (Chem. Rev., 2007)

(untitled) - Beyer, M. K.; Clausen-Schaumann, H. (Chem. Rev., 2005)

(untitled) - Tanaka, K.; Toda, F. (Chem. Rev., 2000)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Zhu, S.-E.; Li, F.; Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Cheng, B.; Cui, S. (Top. Curr. Chem., 2015)

(untitled) - Delori, A.; Friščić, T.; Jones, W. (CrystEngComm, 2012)

(untitled) - Thompson, M. C.; Busch, D. H. (J. Am. Chem. Soc., 1964)

(untitled) - Thompson, M. C.; Busch, D. H. (J. Am. Chem. Soc., 1962)

(untitled) - Leonardi, M.; Villacampa, M.; Menéndez, J. C. (Chem. Sci., 2018)

(untitled) - Saha, M. L.; Mittal, N.; Bats, J. W.; Schmittel, M. (Chem. Commun., 2014)

(untitled) - Nitschke, J. R. (Chem. Soc. Rev., 2014)

(untitled) - Han, M.; Engelhard, D. M.; Clever, G. H. (Chem. Soc. Rev., 2014)

(untitled) - Saha, M. L.; Schmittel, M. (Org. Biomol. Chem., 2012)

(untitled) - Schmittel, M.; Kalsani, V. (Top. Curr. Chem., 2005)

(untitled) - He, Z.; Jiang, W.; Schalley, C. A. (Chem. Soc. Rev., 2015)

(untitled) - Osowska, K.; Miljanić, O. Š. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ji, Q.; Lirag, R. C.; Miljanić, O. Š. (Chem. Soc. Rev., 2014)

(untitled) - Hubin, T. J.; Busch, D. H. (Coord. Chem. Rev., 2000)

(untitled) - Ferguson, M.; Giri, N.; Huang, X.; Apperley, D.; James, S. L. (Green Chem., 2014)

(untitled) - Orita, A.; Jiang, L.; Nakano, T.; Ma, N.; Otera, J. (Chem. Commun., 2002)

(untitled) - Fujita, M.; Yazaki, J.; Ogura, K. (J. Am. Chem. Soc., 1990)

(untitled) - Juribašić, M.; Užarević, K.; Gracin, D.; Ćurić, M. (Chem. Commun., 2014)

(untitled) - Hsueh, S.-Y.; Cheng, K.-W.; Lai, C.-C.; Chiu, S.-H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Hsu, C.-C.; Chen, N.-C.; Lai, C.-C.; Liu, Y.-H.; Peng, S.-M.; Chiu, S.-H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Holler, M.; Stoerkler, T.; Louis, A.; Fischer, F.; Nierengarten, J.-F. (Eur. J. Org. Chem., 2019)

(untitled) - Li, H.-G.; Wang, G.-W. (J. Org. Chem., 2017)

(untitled) - Icli, B.; Christinat, N.; Tönnemann, J.; Schüttler, C.; Scopelliti, R.; Severin, K. (J. Am. Chem. Soc., 2009)

(untitled) - Hai-Gen, L.; Liang, L.; Hui, X.; Guan-Wu, W. (Curr. Org. Chem., 2018)

(untitled) - Pascu, M.; Ruggi, A.; Scopelliti, R.; Severin, K. (Chem. Commun., 2013)

(untitled) - Yang, Y.; Bu, F.; Liu, J.; Shakir, I.; Xu, Y. (Chem. Commun., 2017)

Beauty in Chemistry - Bruns, C. J.; Stoddart, J. F. (The Mechanical Bond: A Work of Art, 2011)

Beauty in Chemistry - Raymond, K. N.; Brown, C. J. (Inner and Outer Beauty, 2012)

(untitled) - Mitra, T.; Jelfs, K. E.; Schmidtmann, M.; Ahmed, A.; Chong, S. Y.; Adams, D. J.; Cooper, A. I. (Nat. Chem., 2013)

(untitled) - Rotzler, J.; Mayor, M. (Chem. Soc. Rev., 2013)

(untitled) - Chakrabarty, R.; Mukherjee, P. S.; Stang, P. J. (Chem. Rev., 2011)

(untitled) - Giuseppone, N. (Acc. Chem. Res., 2012)

(untitled) - Sun, Q.-F.; Iwasa, J.; Ogawa, D.; Ishido, Y.; Sato, S.; Ozeki, T.; Sei, Y.; Yamaguchi, K.; Fujita, M. (Science, 2010)

(untitled) - Ponnuswamy, N.; Cougnon, F. B. L.; Clough, J. M.; Pantos, G. D.; Sanders, J. K. M. (Science, 2012)

(untitled) - Samanta, S. K.; Bats, J. W.; Schmittel, M. (Chem. Commun., 2014)

(untitled) - Su, X.; Aprahamian, I. (Chem. Soc. Rev., 2014)

(untitled) - Osowska, K.; Miljanić, O. Š. (Synlett, 2011)

(untitled) - Ji, Q.; Miljanić, O. Š. (J. Org. Chem., 2013)

(untitled) - Safont-Sempere, M. M.; Fernández, G.; Würthner, F. (Chem. Rev., 2011)

(untitled) - Nitschke, J. R. (Acc. Chem. Res., 2007)

(untitled) - Kassem, S.; van Leeuwen, T.; Lubbe, A. S.; Wilson, M. R.; Feringa, B. L.; Leigh, D. A. (Chem. Soc. Rev., 2017)

(untitled) - Mal, P.; Schultz, D.; Beyeh, K.; Rissanen, K.; Nitschke, J. R. (Angew. Chem., Int. Ed., 2008)

(untitled) - Mal, P.; Breiner, B.; Rissanen, K.; Nitschke, J. R. (Science, 2009)

(untitled) - Giri, C.; Sahoo, P. K.; Puttreddy, R.; Rissanen, K.; Mal, P. (Chem. – Eur. J., 2015)

(untitled) - Sahoo, P. K.; Bose, A.; Mal, P. (Eur. J. Org. Chem., 2015)

(untitled) - Schultz, D.; Nitschke, J. R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Belenguer, A. M.; Friščić, T.; Day, G. M.; Sanders, J. K. M. (Chem. Sci., 2011)

(untitled) - Herrmann, A. (Chem. Soc. Rev., 2014)

(untitled) - Carnall, J. M. A.; Waudby, C. A.; Belenguer, A. M.; Stuart, M. C. A.; Peyralans, J. J.-P.; Otto, S. (Science, 2010)

(untitled) - Kaabel, S.; Stein, R. S.; Fomitšenko, M.; Järving, I.; Friščić, T.; Aav, R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Jin, Y.; Wang, Q.; Taynton, P.; Zhang, W. (Acc. Chem. Res., 2014)

(untitled) - Jin, Y.; Yu, C.; Denman, R. J.; Zhang, W. (Chem. Soc. Rev., 2013)

(untitled) - Atkinson, M. B. J.; Bučar, D.-K.; Sokolov, A. N.; Friščić, T.; Robinson, C. N.; Bilal, M. Y.; Sinada, N. G.; Chevannes, A.; MacGillivray, L. R. (Chem. Commun., 2008)

(untitled) - Journey, S. N.; Teppang, K. L.; Garcia, C. A.; Brim, S. A.; Onofrei, D.; Addison, J. B.; Holland, G. P.; Purse, B. W. (Chem. Sci., 2017)

(untitled) - Georghiou, P. E.; Schneider, C.; Shamov, G.; Lash, T. D.; Rahman, S.; Sabrina Giddings, D. (Supramol. Chem., 2016)

(untitled) - Vriezema, D. M.; Comellas Aragonès, M.; Elemans, J. A. A. W.; Cornelissen, J. J. L. M.; Rowan, A. E.; Nolte, R. J. M. (Chem. Rev., 2005)

Non-covalent Interactions in the Synthesis and Design of New Compounds - Maharramov, A. M.; Mahmudov, K. T.; Kopylovich, M. N.; da Silva, M. F. C. G.; Pombeiro, A. J. L. (Activation of Covalent Bonds Through Non-covalent Interactions, 2016)

Noncovalent Interactions in Catalysis - Bose, A.; Maiti, S.; Mal, P. (Soft Forces in Organic Synthesis by C–N Coupling Reactions, 2019)

(untitled) - Amendola, V.; Fabbrizzi, L.; Mosca, L. (Chem. Soc. Rev., 2010)

(untitled) - Dougherty, D. A. (Acc. Chem. Res., 2013)

(untitled) - Kennedy, C. R.; Lin, S.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2016)

(untitled) - Achar, T. K.; Maiti, S.; Mal, P. (Org. Biomol. Chem., 2016)

(untitled) - Giese, M.; Albrecht, M.; Rissanen, K. (Chem. Rev., 2015)

(untitled) - Li, C.-J. (Chem. Rev., 2005)

(untitled) - Percástegui, E. G.; Mosquera, J.; Nitschke, J. R. (Angew. Chem., Int. Ed., 2017)

(untitled) - Breugst, M.; von der Heiden, D.; Schmauck, J. (Synthesis, 2017)

(untitled) - Bulfield, D.; Huber, S. M. (Chem. – Eur. J., 2016)

(untitled) - Cavallo, G.; Metrangolo, P.; Pilati, T.; Resnati, G.; Sansotera, M.; Terraneo, G. (Chem. Soc. Rev., 2010)

(untitled) - Turunen, L.; Warzok, U.; Schalley, C. A.; Rissanen, K. (Chem, 2017)

(untitled) - Sokolov, A. N.; Bučar, D.-K.; Baltrusaitis, J.; Gu, S. X.; MacGillivray, L. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Stojaković, J.; Farris, B. S.; MacGillivray, L. R. (Chem. Commun., 2012)

(untitled) - Lisac, K.; Topić, F.; Arhangelskis, M.; Cepić, S.; Julien, P. A.; Nickels, C. W.; Morris, A. J.; Friščić, T.; Cinčić, D. (Nat. Commun., 2019)

(untitled) - Kumar Achar, T.; Mal, P. (Adv. Synth. Catal., 2015)

(untitled) - Bose, A.; Maiti, S.; Sau, S.; Mal, P. (Chem. Commun., 2019)

Hypervalent Iodine Chemistry - Murarka, S.; Antonchick, A. P. (Oxidative Heterocycle Formation Using Hypervalent Iodine(III) Reagents, 2015)

(untitled) - Ribas-Arino, J.; Shiga, M.; Marx, D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ribas-Arino, J.; Marx, D. (Chem. Rev., 2012)

(untitled) - Friščić, T.; Halasz, I.; Beldon, P. J.; Belenguer, A. M.; Adams, F.; Kimber, S. A. J.; Honkimäki, V.; Dinnebier, R. E. (Nat. Chem., 2013)